(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2024)
Background: Transesophageal Echocardiography (TEE) is superior in identifying potential cardiac sources of emboli in stroke workup. But it is more costly and difficult to perform than Transthoracic Echocardiography (TTE). Moreover, facilities for TEE are not evenly distributed in Bangladesh. The study aimed to assess the diagnostic accuracy of TTE in detecting the cardiac source of emboli in admitted ischemic stroke patients in a Neurology ward of a tertiary hospital in Bangladesh. Materials and methods: Ninety-two consecutively admitted patients admitted with a diagnosis of ischemic stroke without any preexisting indication of anticoagulation and known heart disease were enrolled in this study from the Neurology ward of Chittagong Medical College Hospital (CMCH) Chattogram, Bangladesh. All patients were underwent TTE and TEE. Results: Mean age was 48.36±12.64 years with male predominance (Male to Female ratio was 1.88: 1). Eleven cardioembolic sources were detected by TEE (8 Left atrial appendage thrombus, 2 patent foramen ovale and 1 mild mitral stenosis) in 10 patients. Among these TTE could identify only one case (mild mitral stenosis). The sensitivity, specificity, positive predictive value, negative predictive value, and overall accuracy of TTE to detect cardioembolic sources were 10%, 100%, 100%, 90.11% and 90.22% respectively. Conclusion: Diagnostic yield of TTE was very low in detecting the cardiac source of embolism in selected patients with ischaemic stroke. Chatt Maa Shi Hosp Med Coll J; Vol.22 (2); July 2023; Page 68-71